The Role of Women in Empowering Family Economy through Agriculture in Koro Village - Nuryati, Mariam Nona; Djono, Ammir; Chotimah, Nur (International Journal Labs, 2022)
Background: Women have an important role in life. In modern times, women have roles in various aspects, one of which is agriculture. Aim: The purpose of this research is to find out (1) the role of women, (2) how the efforts to empower the family‘s economy are carried out by women through agriculture. Method: This type of research is collection methods namely observation, interviews, and documentation. Findings: The results of this study indicate (1) the role of women in the village of Ubamoro Koro Bhera village in addition to being a housewife but also as a farm laborer by working on someone else‘s land, (2) the main factors causing women to work are to meet household needs due to low-income husband, (3) wages earned by farm laborers are 5000/hour of work.